Attachment of Asaia bogorensis Originating in Fruit-Flavored Water to Packaging Materials. (10th September 2014) - Kregiel, Dorota; Otlewska, Anna; Antolak, Hubert
Abstract : The objective of this study was to investigate the adhesion of isolated spoilage bacteria to packaging materials used in the food industry. Microorganisms were isolated from commercial fruit-flavored mineral water in plastic bottles with flocks as a visual defect. The Gram-negative rods were identified using the molecular method through the amplification of a partial region of the 16S rRNA gene. Based on the sequence identity (99.6%) between the spoilage organism and a reference strain deposited in GenBank, the spoilage isolate was identified as Asaia bgorensis . Experiments on bacterial adhesion were conducted using plates made of glass and polystyrene (packaging materials commonly used in the beverage industry). Cell adhesion ability was determined using luminometry, plate count, and the microscopic method. The strain of A. bogorensis was characterized by strong adhesion properties which were dependent on the surface type, with the highest cell adhesion detected on polystyrene.